CENTRALISED MULTI-NATIONAL PRACTICES OF TRANSFER AND MANAGERIAL DISCREPANCIES: EVIDENCE FROM A ROMANIAN CALL CENTER - MIHÁLY, Zoltan (Studia Universitatis Babeș-Bolyai Sociologia, 2021)
This paper describes workplace dynamics in a call centre located in Romania, a subsidiary of a multi-national corporation (MNC). Positing a centralised practice transfer and global management strategy, the company relies exclusively on home-country decision makers. Placed within Romania’s dependent economic profile alongside its deregulated employment relations, centralised managerial decisions create widespread organisational uncertainty with numerous hire and fire and downsizing procedures, followed by subsequent recruitment campaigns designed to replace the previously displaced workforce.